l-Citrulline Protects from Kidney Damage in Type 1 Diabetic Mice - Romero, Maritza J.; Yao, Lin; Sridhar, Supriya; Bhatta, Anil; Dou, Huijuan; Ramesh, Ganesan; Brands, Michael W.; Pollock, David M.; Caldwell, Ruth B.; Cederbaum, Stephen D.; Head, C Alvin; Bagi, Zsolt; et al. (Frontiers in Immunology, 2013)
Rationale. Diabetic nephropathy is a major cause of end-stage renal disease, associated with endothelial dysfunction. Chronic supplementation of L-arginine (L-arg), the substrate for endothelial nitric oxide synthase (eNOS), failed to improve vascular function. L-citrulline (L-cit) supplementation not only increases L-arg synthesis, but also inhibits cytosolic arginase I (Arg I), a competitor of eNOS for the use of L-arg, in the vasculature. Aims. To investigate whether L-cit treatment reduces diabetic nephropathy in streptozotocin (STZ)-induced type 1 diabetes in mice and rats and to study its effects on arginase II (ArgII) function, the main renal isoform. Methods. STZ-C57BL6 mice received L-cit or vehicle supplemented in the drinking water. For comparative analysis, diabetic ArgII knock out mice and L-cit-treated STZ-rats were evaluated. Results. L-cit exerted protective effects in kidneys of STZ-rats, and markedly reduced urinary albumin excretion, tubulo-interstitial fibrosis and kidney hypertrophy, observed in untreated diabetic mice. Intriguingly, L-cit treatment was accompanied by a sustained elevation of tubular ArgII at 16 wks and significantly enhanced plasma levels of the anti-inflammatory cytokine IL-10. Diabetic ArgII knock out mice showed greater BUN levels, hypertrophy, and dilated tubules than diabetic wild type mice. Despite a marked reduction in collagen deposition in ArgII knock out mice, their albuminuria was not significantly different from diabetic wild type animals. L-cit also restored NO/ROS balance and barrier function in high glucose-treated monolayers of human glomerular endothelial cells. Moreover, L-cit also has the ability to establish an anti-inflammatory profile, characterized by increased IL-10 and reduced IL-1beta and IL-12(p70) generation in the human proximal tubular cells. Conclusions. L-cit supplementation established an anti-inflammatory profile and significantly preserved the nephron function during type 1 diabetes.